Déclin ou redéploiement ? La sociologie du travail au Royaume-Uni - Carol Stephenson; Paul Stewart (La Nouvelle Revue du Travail)
This paper takes issue with once influential accounts regarding the development and current power of the Sociology of work (SoW) in the UK by challenging the mythologies that have arisen in this sub-discipline’s wake. It relies on a sociological analysis of the political, organisational and social forces that have shaped this branch in question, as well as on a comprehensive examination of its broad and complex canon. The approach enables a refutation of previous orthodoxies suggesting that a clearly defined SoW only existed previously in (and emerged from) the narrow confines of Sociology departments - and that a ‘Golden Age’ of SoW research therefore existed in the post-WWII era, one whose demise inexorably led to the sub-discipline’s own decline. These misinterpretations are politically problematic in that they laud an era of research that neglected complex and important questions relating to who holds power; how such power is exercised; and how social inequality is reproduced through work and employment. Critical feedback has revealed that such interpretations of SoW are far too narrow. The paper overturns conventional wisdom about the sub-discipline’s contemporary importance and relevance. Where others have identified decline, it explores SoW’s relationship to power and inequality as well as the scope of its impact - concluding that it has far spread beyond the narrow confines of academia and therefore offers a real opportunity for radical social change.